2018
DOI: 10.9734/ijpss/2018/40960
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis for Forage Agronomic Crops Grown Using Treated Wastewater in Kherbeh Als-Samra Region, Jordan

Abstract: Regarding Jordan's apparent climate change, the urgent need to use treated wastewater for irrigation and the production of forage crops has become an imperative. The possibilities for growing highly profitable forage crops using treated wastewater are discussed in the case of extension demonstrations in Kherbeh Als-Samra region. The economic analysis for extension demonstrations of Kherbeh Als-Samra region is presented. The case report has been prepared in the Zarqa Extension Unit, National Center for Agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Many studies have found similar results and emphasized the importance of crop rotations within agricultural development plans. Similar findings were reported for forage agronomic crops in Jordan using treated wastewater (Massimi et al, 2018). Agricultural crop rotations are environmentally safe methods to control pests and procedures for obtaining a healthy food product.…”
supporting
confidence: 82%
“…Many studies have found similar results and emphasized the importance of crop rotations within agricultural development plans. Similar findings were reported for forage agronomic crops in Jordan using treated wastewater (Massimi et al, 2018). Agricultural crop rotations are environmentally safe methods to control pests and procedures for obtaining a healthy food product.…”
supporting
confidence: 82%